Pengaruh Perkeretaapian Terhadap Perkembangan Struktur Tata Ruang Kota Cirebon Berdasarkan Tinggalan Arkeologis - Iwan Hermawan; Octaviadi Abrianto; Revi Mainaki (Pusat Penelitian Arkeologi Nasional, 2020)
Abstract. Cirebon is a strategic city in the north of Java which, based on concentric theory, has a dynamic development process. This research used a qualitative approach and the descriptive method followed the pattern of inductive reasoning where data was collected through a) a literature study to documents from Indonesian National Archives (ANRI) and PT KAI Indonesia; b) field survey to observe the remains of the railroads; and c) interviews with the community leaders. Data were then analyzed spatially, using indicators from concentric theory, to see the effect of railroads on the development of the spatial structure of Cirebon. The result of the study reveals that the palace used to be the center of community activities during the kingdom reign, then shifted after the Dutch arrived and built the railroads. The center of the activities shifted to the ports, the stations, along the train stops, the plantation areas, the sugar factories, and the meeting points of the roads. The remains of the railroads today become a contextual proof of the development of the spatial structure of Cirebon which must be preserved as an archaeological value. Keywords: Train Heritage, Spatial Structure, Cirebon Abstrak. Cirebon merupakan kota yang strategis di bagian utara Pulau Jawa. Jika didasarkan pada teori konsentris, kota ini memiliki proses perkembangan dinamis. Penelitian ini menggunakan pendekatan kualitatif, metode deskripstif mengikuti pola penalaran induktif. Data dikumpulkan melalui studi literatur, yakni dokumen dari Arsip Nasional Indonesia dan PT KAI Indonesia; survei untuk melihat sisa tinggalan perkeretaapian dari studi literasi; dan wawancara kepada tokoh masyarakat. Data dianalisis secara spasial dengan indikator dari teori konsentris untuk melihat pengaruh perkeretaapian terhadap perkembangan struktur tata ruang Kota Cirebon. Hasil penelitian tinggalan arkeologis perkeretaapian menunjukan bahwa pada masa kerajaan, pusat aktivitas masyarakat berada di sekitar keraton, kemudian bergeser setelah Belanda datang dan membangun perkeretaapian. Pusat aktivitas bergeser ke pelabuhan, stasiun, sepanjang perhentian kereta api, kawasan perkebunan, pabrik gula dan titik pertemuan jalan. Kondisi tinggalan tersebut menjadi bukti kontekstual perkembangan struktur tata ruang Kota Cirebon yang harus dilestarikan sebagai peninggalan bernilai arkeologis. Kata kunci: Tinggalan Perkeretaapian, Struktur Tata Ruang, Cirebon